A displaced T type intercondylar distal humerus fracture with radial nerve palsy in a 10-year-old treated by closed reduction and K wire fixation - Nair, Nikhilesh; Sameer, Mohamed; Giriraj, J. K.; Navaneeth, Ghantasala (International Journal of Research in Orthopaedics, 2022)
T type intercondylar fractures of the distal hummers in the pediatric age group is an extremely rare injury. These fractures are difficult to diagnosed as they can be mistaken for extension type injuries. The few clinal trials on the management of the fracture, it is widely regarded that the accepted method of treatment is open reduction and rigid internal fixation. It is easier to ensure stable articular reconstruction of the intra articular fragments by this method. Open reduction and internal fixation of there fractures are associated with high complication rate, which include wound site problems, non-union due to periosteal stripping, heterotrophic ossification and iatrogenic nerve injury. Large soft tissue dissection can also lead to vascular compromise and significant scar tissue which is associated with a stiff elbow. We present a case of a 10-year-old boy who sustained an intercondylar fracture with radial nerve palsy which was treated by closed reduction and Kirshner wire fixation with excellent results at 1 year follow up.